Promotional Features And Electronic Wallets Drive Student Consumptive Behavior: Fitur Promo Dan Dompet Elektronik Mendorong Perilaku Konsumtif Mahasiswa - Dwi Maya Rahmawati; M. Farid Hilmi Najim; Eko Satriyo Hadi Nata; Vicky Dwi Hariyanto; Sigit Hermawan (International Consortium of Education and Culture Research Studies, 2024)
General Background The rapid advancement of digital financial technology has revolutionized cashless payment systems globally. Specific Background Payment applications provide users with seamless transaction capabilities and various marketing incentives, which heavily attract university scholars. Knowledge Gap Despite the widespread adoption of these digital payment platforms, empirical studies show inconsistencies regarding how specific software attributes and marketing incentives shape excessive spending habits. Aims This study investigates the role of perceived convenience and promotional offerings in shaping scholar spending habits, utilizing payment applications as a mediating variable. Results Path analysis of data from university scholars indicates that promotional offerings significantly stimulate platform adoption, whereas perceived convenience does not determine application usage. Furthermore, both perceived convenience and promotional offerings directly stimulate excessive spending. Payment applications also act as a significant mediator, primarily translating promotional offerings into impulsive purchasing habits. Novelty This research demonstrates that marketing incentives, rather than platform usability, are the primary catalysts triggering application adoption and subsequent impulsive purchasing among scholars. Implications Developers and financial regulators must recognize that aggressive marketing incentives within digital payment ecosystems strongly trigger impulsive purchasing, necessitating better financial literacy initiatives for young consumers. Highlights: Marketing incentives significantly increase platform adoption rates among young adults. Perceived convenience shapes purchasing habits directly without relying on application usage. Cashless payment applications successfully mediate the pathway between discount offerings and excessive spending. Keywords: Digital Payment Platforms, Perceived Convenience, Marketing Incentives, Excessive Spending, Mediating Variable